2017
DOI: 10.1136/bmjopen-2017-016501
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile and pregnancy outcomes of adolescents and older mothers in Saudi Arabia: analysis from Riyadh Mother (RAHMA) and Baby cohort study

Abstract: ObjectivesTo investigate the impact of maternal age on pregnancy outcomes with special emphasis on adolescents and older mothers and to investigate the differences in demographic profile between adolescents and older mothers.MethodsThis study is a secondary analysis of pregnancy outcomes of women in Riyadh Mother and Baby cohort study according to maternal age. The study population was grouped according to maternal age into five subgroups; <20, 20–29, 30–34, 35–39 and 40+years. The age group 20–29 years was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 40 publications
8
36
1
Order By: Relevance
“…join age was not similar to the threshold age after which the risk of specific adverse outcomes started to increase statistically significantly as compared with the reference age. Our results were in line with those of previous studies on the effect of maternal age (analyzed by age groups), and the risks of adverse pregnancy and birth outcomes increased in both younger (<20 years) 12,13 and older (≥35 years) mothers. [14][15][16] Therefore, there is good reason to believe that most of our results for the association of adolescent and advanced maternal age with adverse pregnancy outcomes are applicable to other reports.…”
Section: Ta B L E 1 the Baseline Characteristics In Primiparasupporting
confidence: 92%
“…join age was not similar to the threshold age after which the risk of specific adverse outcomes started to increase statistically significantly as compared with the reference age. Our results were in line with those of previous studies on the effect of maternal age (analyzed by age groups), and the risks of adverse pregnancy and birth outcomes increased in both younger (<20 years) 12,13 and older (≥35 years) mothers. [14][15][16] Therefore, there is good reason to believe that most of our results for the association of adolescent and advanced maternal age with adverse pregnancy outcomes are applicable to other reports.…”
Section: Ta B L E 1 the Baseline Characteristics In Primiparasupporting
confidence: 92%
“…The BW increased faster from age 20 until age 23 than from age 24 until age 34. The curve was consistent with the ndings of the previous studies [12,14]. But no research provided the threshold maternal age on BW was 34 years old [12,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies indicated that the relationship between maternal age and birth weight was inconsistent [4,12,[14][15][16]. Most of the previous studies focused on the incidence of LWB and macrosomia in different age groups by xed classi cation of maternal age [14,16], which might underestimate age-related risk for women in younger age groups and overestimate risks for mothers in older age groups [17]. There is no su cient evidence to assess the appropriateness of using this arti cial traditional age classi cation to assess their impacts on BW.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental exposures included smoking and secondhand smoking [49,56], and all six studies on anthropometric measures were on BMI (Table 1 and see Additional file 3: Table S2). [47,50,53,54,83,111,113], and maternal anemia in three cohort studies [50,104,113]. Postpartum depression was explored in only one prospective cohort study in the UAE [76].…”
Section: Other Exposuresmentioning
confidence: 99%
“…Summary of the reviewed 81 published cohort studies according to the measured six exposure and two outcome domainsSociodemographic exposuresMaternal age was a common measured sociodemographic exposure studied in 18 cohort studies. Advanced maternal age was associated with GDM, CS, and preterm delivery[51,53,58,92,111,113]. Primary education or less was independently associated with 69% lower likelihood of exclusive breastfeeding at 6 months (aOR, 0.31; 95% CI, 0.11-0.88)[58] (see Additional file 3:Table S2).…”
mentioning
confidence: 99%